2013
DOI: 10.1111/tct.12027
|View full text |Cite
|
Sign up to set email alerts
|

Implementing student self-video of performance

Abstract: Web-based student self-video of performance, with remote tutor feedback and guided reflection, is a feasible method for increasing students' capacity for reflection and self-evaluation. Although technical difficulties are inherent in any technology-reliant activity, the students' increasing competence with emerging technologies encourage self-video teaching and learning activities as a resource for facilitating clinical skill development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…These findings coincide with the notion that traditional Continuing Medical Education formats and passive approaches have little effect on behavior change [17,18] and that self-video analysis, when used as a supplement to traditional teaching methods, corresponds with greater clinical skill competency and more effective use of feedback. [19] Finally, our in-depth single case study of behavioral and physiologic parameters showed a clear pattern of the potential regulatory effects of small changes in nurse caregiving. To our surprise, the intentional introduction had the most regulatory effect on the time period after care.…”
Section: Discussionmentioning
confidence: 79%
“…These findings coincide with the notion that traditional Continuing Medical Education formats and passive approaches have little effect on behavior change [17,18] and that self-video analysis, when used as a supplement to traditional teaching methods, corresponds with greater clinical skill competency and more effective use of feedback. [19] Finally, our in-depth single case study of behavioral and physiologic parameters showed a clear pattern of the potential regulatory effects of small changes in nurse caregiving. To our surprise, the intentional introduction had the most regulatory effect on the time period after care.…”
Section: Discussionmentioning
confidence: 79%
“…Interesting, the students also generally scored their own performance lower than that of peers and the teacher. A slight variant to this approach, but with similar positive findings by McNulty and Lazarevic (2012) and Maloney et al (2013) used video recordings in a role play format. The outcomes of the studies could have been improved if the study compared if the video was able to improve live presentation skills.…”
Section: Related Workmentioning
confidence: 94%
“…The use of video feedback has been used across many disciplines over a long period of time as an effective method to improve learning and provide effective feedback. Examples include: teacher development and training (Abbott, Wulff, and Szego 1989;Nikolic et al 2015), enhancing the learning of concepts (Lee and Lehto 2013;Vial et al 2015;, developing authentic learning experiences (Kearney and Schuck 2006;Rodriguez, Ajjan, and Honeycutt 2014), and most important to this study improving learning via feedback (Barry 2012;Maloney et al 2013;Hsia, Huang, and Hwang 2016). The advantages of the video medium, is that it is a multi-sensory environment and that students are exposed to it in their daily lives (McNulty and Lazarevic 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While, some studies highlight the value of students using the smartphone video app feature to learn psychomotor skills in nursing, midwifery and medicine. [34][35][36][37][38][39] Some faculties and managers resist the use of smartphones among nursing students in the classroom and during clinical practice, and further describe it as being addictive; [40] rude; [41] distracting; [42,43] creating a physically present but mentally absent user; [44] unprofessional, unethical and time-wasting. [45] However, other studies demonstrate that with appropriate technical and pedagogical support from faculty, the use of the smartphone in the classroom and as an e-learning tool not only improves students' engagement, but also prepares them for ever-changing technologies in delivering healthcare.…”
Section: Background and Literature Reviewmentioning
confidence: 99%